PENGARUH MODERNISASI PERTANIAN TERHADAP KEHIDUPAN SOSIAL EKONOMI MASYARAKAT DI KAMPUNG YANAMEK DISTRIK ABENAHO KABUPATEN YALIMO - Johni Siep; Johni Jonatan Numberi; Arung Lamba (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2022)
Agriculture is part of the culture that was first developed by humans as a response to the challenges of survival which gradually became difficult due to the depletion of food sources in the wild due to the rate of human growth. In addition, agriculture as a system in human life aims to produce vegetable and animal materials including aquatic biota (water) by using natural and water resources effectively and efficiently in order to achieve the welfare of human life and the preservation of the carrying capacity of the environment. The results showed that the use of agricultural land from the aspect of meeting basic needs in the form of housing, clothing and food can be said to be high after the utilization of agricultural land. This can be seen from the number of people who have permanent housing in the sense that there has been rehabilitation of the floors and walls of the house. What used to be an earthen floor and clapboard walls, now has a cement or tile floor and the walls are made of walls or ceramics. Indeed, there are still respondents who do not have housing because housing has been provided by the relevant agency specifically for civil servants or teachers who are placed in schools that already have housing. Likewise, the fulfillment of clothing and food needs can be said to be very fulfilled